Listen, slowly - e uthor (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
Assisting her grandmother's investigation of her grandfather's fate during the Vietnam War, Mai struggles to adapt to an unfamiliar culture while redefining her sense of family.
Ages 8-12.
Keywords: Grandmothers -- Juvenile fiction; Vietnam War, 1961-1975 -- Missing in action -- Juvenile fiction; Families -- Juvenile fiction; Vietnam -- Juvenile fiction; Grandmothers -- Fiction; Vietnam War, 1961-1975 -- Missing in action -- Fiction; Family life -- Fiction; Vietnam -- Fiction; 1961 - 1975